Synthesis of the major viral proteins under conditions of the mixed infection of cells MDBK - Biliavska, L. O.; Povnitsa, O. Y.; Zagorodnya, S. D.; Nesterova, N. V.; Shamara, Y. B.; Naumenko, K. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
A model of mixed adeno-herpetic infection of MDBK cells is created. The levels of the synthesis of the major proteins of adenoviruses and herpes viruses under conditions of the mixed infection are studied. Simultaneous infection of cells with two viruses resulted in a significant inhibition of the reproduction of the herpes virus and a less pronounced inhibition of the adenovirus reproduction.